2008
DOI: 10.1002/ps.1550
|View full text |Cite
|
Sign up to set email alerts
|

Early timing and new combinations to increase the efficacy of neonicotinoid–entomopathogenic nematode (Rhabditida: Heterorhabditidae) combinations against white grubs (Coleoptera: Scarabaeidae)

Abstract: Imidacloprid is a better synergist for entomopathogenic nematodes than clothianidin. Imidacloprid-nematode combinations are more effective against second instars than against third instars, allowing rate reductions of both agents to make this approach more competitive with full-rate applications of neonicotinoid alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Thus such combinations can be used to enhance pest control. In terms of combinations with chemical insecticides, a body of research indicates that neonicotinoids can be synergistically combined with EPNs for control of scarab pests (Koppenhöfer & Fuzy, 2008;Morales-Rodriguez & Peck, 2009). Yet recent research indicated only additive or antagonistic interactions for the control of Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae) (Navarro, McMullen, & Stock, 2014), which again emphasizes the variation that exists among EPN and host species.…”
Section: Improved Methods Of Applicationmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus such combinations can be used to enhance pest control. In terms of combinations with chemical insecticides, a body of research indicates that neonicotinoids can be synergistically combined with EPNs for control of scarab pests (Koppenhöfer & Fuzy, 2008;Morales-Rodriguez & Peck, 2009). Yet recent research indicated only additive or antagonistic interactions for the control of Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae) (Navarro, McMullen, & Stock, 2014), which again emphasizes the variation that exists among EPN and host species.…”
Section: Improved Methods Of Applicationmentioning
confidence: 98%
“…Composted manure may be beneficial to EPN by reducing natural enemies, e.g., nematophagous fungi (Duncan et al, 2007). Some chemical pesticides are harmful to EPNs (e.g., abamectin, acephate, aldicarb, dodine, fenamiphos, methomyl, parathion, and teflubenuron), whereas others tend to be compatible and in some cases may be synergistic when applied with EPNs (e.g., carbaryl, chlorpyrifos, dimethoate, endosulfan, fonofos, tefluthrin, imidicloprid) (Alumai & Grewal, 2004;Koppenhöfer & Fuzy, 2008;Koppenhöfer & Grewal, 2005;Koppenhöfer & Kaya, 1998;Nishimatsu & Jackson, 1998;Shapiro-Ilan, Cottrell, & Wood, 2011). Akin to interactions with other microbial agents, the relationship between chemical pesticides and EPNs depends on the particular chemical and nematode species or population, dosages, and timing of application (Benz, 1971;Koppenhöfer & Grewal, 2005), and therefore specific combinations should be tested on a case-by-case basis.…”
Section: Abiotic Factorsmentioning
confidence: 99%
“…tenebrionis and entomopathogenic fungi (also in combination with EPNs) achieved satisfactory results for grub control. The late August application also proved suitable for grub control in related research conducted by Koppenhöfer and Fuzy (2008). The lower efficacy of the biological control agents in the spring application could be related to the soil temperature.…”
Section: Discussionmentioning
confidence: 90%
“…Such combinations have been studied extensively for soil insects and were particularly strong with the neonicotinoid insecticide imidacloprid against scarab beetle larvae (Koppenhöfer & Grewal, 2005, and references therein;Koppenhöfer & Fuzy, 2008). Very little is known about such interactions for above-ground insect pests.…”
Section: Introductionmentioning
confidence: 98%
“…Mortality data in the combination experiment were arcsine square-root transformed and analysed using ANOVA followed by means separation, using Tukey's test (SAS Institute, 2004). Synergistic, additive or antagonistic interactions between agents in the combination treatments were determined using a χ 2 test (Koppenhöfer & Fuzy, 2008). The expected additive proportional mortality M E for the combinations was calculated by M E ¼ M N þ M I ð1 À M N Þ, where M N and M I are the observed proportional mortalities caused by nematodes and imidacloprid alone, respectively.…”
mentioning
confidence: 99%